Coupling of PZT Thin Films with Bimetallic Strip Heat Engines for Thermal Energy Harvesting - Jihane Boughaleb; Arthur Arnaud; Benoit Guiffard; Daniel Guyomar; Raynald Seveno; Stéphane Monfray; Thomas Skotnicki; Pierre-Jean Cottinet (Sensors, 2018)
A thermal energy harvester based on a double transduction mechanism and which converts thermal energy into electrical energy by means of piezoelectric membranes and bimetals, has previously been developed and widely presented in the literature In such a device, the thermo-mechanical conversion is ensured by a bimetal whereas the electro-mechanical conversion is generated by a piezoelectric ceramic. However, it has been shown that only 19% of the mechanical energy delivered by the bimetal during its snap is converted into electrical energy. To extract more energy from the bimetallic strip and to increase the transduction efficiency, a new way to couple piezoelectric materials with bimetals has thus been explored through direct deposition of piezoelectric layers on bimetals. This paper consequently presents an alternative way to harvest heat, based on piezoelectric bimetallic strip heat engines and presents a proof of concept of such a system. In this light, different PZT (Lead zirconate titanate) thin films were synthesized directly on aluminium foils and were attached to the bimetals using conductive epoxy. The fabrication process of each sample is presented herein as well as the experimental tests carried out on the devices. Throughout this study, different thicknesses of the piezoelectric layers and substrates were tested to determine the most powerful configuration. Finally, the study also gives some guidelines for future improvements of piezoelectric bimetals.